Platelet Activation and Reactivity in a Large Cohort of Patients with Gaucher Disease - Revel-Vilk, Shoshana; Naamad, Mira; Frydman, Dafna; Freund, Michael R.; Dinur, Tama; Istaiti, Majdolen; Becker-Cohen, Michal; Falk, Roni; Broide, Eti; Michelson, Alan D.; Frelinger, Andrew L., III; Zimran, Ari (Thrombosis and Haemostasis, 2021)
Objectives Patients with Gaucher disease (GD) are at increased risk of bleeding and have varying degrees of thrombocytopenia, making the analysis of platelet function difficult. This study aimed to provide a clinically relevant quantitative assessment of platelet function and determine its relationship with bleeding and GD-related data.Methods Unstimulated and stimulated platelet function was measured by whole blood flow cytometry of platelet surface-activated αIIbβ3 integrin (detected with monoclonal antibody PAC1), P-selectin (CD62P), and lysosomal-associated membrane protein (LAMP3/CD63) in 149 GD patients.Results GD patients had a higher level of unstimulated CD63 expression than healthy subjects, which was mildly correlated with glucosylsphingosine (lyso-Gb1) levels (r = 0.17, p-value = 0.042). Splenectomized GD patients had a higher level of unstimulated αIIbβ3 integrin and P-selectin expression. Reduced platelet reactivity (−2 standard deviation of reference range) was found in 79 (53%, 95% confidence interval [CI]: 44–61%) patients, of whom 10 (6.7%, 95% CI: 3.3–12%) had more severe platelet dysfunction. In a multivariate model, only lyso-Gb1 levels were associated with the more severe platelet dysfunction. Fifty-four (49%) of 128 adult patients who completed the bleeding tendency questionnaire reported positive bleeding history. In a multivariate logistic model, older age (odds ratio [OR]: 1.05, 95% CI: 1.01–1.1) and low P-selectin reactivity (OR: 2.03, 95% CI: 1.25–3.35) were associated with more than one bleeding manifestation.Conclusion Flow cytometry enables the study of platelet function in thrombocytopenic GD patients. A platelet degranulation defect, but not αIIbβ3 integrin activation defect, is associated with clinical bleeding. In vivo increased CD63 expression may be related to GD-related inflammation.
Keywords: bleeding; flow cytometry; Gaucher disease; platelet activation; platelet function